Implementation of ISAK No. 35 on the presentation of financial statements of non-profit-oriented entities (Study at GMIM Bukit Hermon Malalayang) - Rompas, Debora Helen; Saerang, David Paul Elia; Lambey, Robert (The Contrarian : Finance, Accounting, and Business Research, 2024)
ISAK No. 35 can be used as a reference in preparing non-profit-oriented financial reporting. One non-profit oriented entity is a church, in this case, the Evangelical Christian Church in Minahasa (or often called GMIM). This study was carried out at GMIM Bukit Hermon Malalayang which is located in Malalayang District, Manado City. This study aims to examine the preparation of church financial reports based on ISAK No. 35 at GMIM Bukit Hermon Malalayang. The study method used is a qualitative approach based on case studies. The results show that the presentation of GMIM Bukit Hermon Malalayang's financial reports has not implemented ISAK No. 35 concerning the presentation of financial statements of non-profit-oriented entities. However, financial reporting is simply based on the GMIM Synod Treasury Supervision and Management Service Guidelines. During the 2023 period, financial reporting has been adjusted to ISAK No. 35 which consists of a comprehensive income report, change in net assets report, financial position report, cash flow report and notes to financial reports.